Job satisfaction and its contributing factors amoung faculty members of Semnan university of medical sciences - Namat Sotodeh Asl (Majallah-i ̒Ilmī-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Simnān, 2012)
Introduction: Skilled and motivated workforce is the most important asset of any organization. The progress of any society depends on the protection and proper utilization of human resources and the academic elite .This study was designed to investigate the job satisfaction rate and its related factors on the faculty members of Semnan University of Medical Sciences (SUMS) in Iran.Materials and Methods: This study was conducted in 2012 in SUMS. 83 faculty members of SUMS participated in this study. Job satisfaction questionnaire Smith, Kendall and Hulin demographic questionnaires were used for data collection.Results: The results showed that the participants expressed their job satisfaction as 15.7% with low satisfaction, 66.2% with moderate satisfaction and 18.1% with high satisfaction.The highest levels of job satisfaction have been in the nature of work and the lowest were in the job satisfaction rights and benefits. There was no significant difference in the areas of job satisfaction between men and women, degrees, and academic degrees. The option of "The pleasure of teaching and work in University and serving the scientific community" has had the highest level of satisfaction. Lack of encouragement and appropriate feedback system has been reported as a reason of the lowest satisfaction.Conclusion: The findings show that a proper evaluation system that leads to timely feedback of performance of faculty member is necessary. The activation of "Office of Industrial Relations" is a useful step in more community usage of faculty member empowering and enhancing their job satisfaction